Study of role of tablet misoprostol and extra amniotic normal saline in second trimester abortion - Kothadiya, Zinkal P.; Airao, Bhavesh B.; Shah, Bipin R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Second-trimester pregnancy termination comprises 10 to 15 percent of the approximately 42 million abortions performed annually worldwide. Second-trimester procedures can be performed either with medication or by mechanical methods (Foleys catheter) or surgically by dilation and evacuation (D and E) or hysterotomy. The objective of the present study was to evaluate and compare the efficacy and safety of Tablet Misoprostol and extra amniotic infusion of normal saline with balloon catheter in second trimester abortion, to find out the maternal outcome, to compare the induction- to delivery interval between tablet misoprostol and extra amniotic infusion of normal saline with balloon catheter and to compare the cost of induction between tablet misoprostol and extra amniotic infusion of normal saline with balloon catheter. Methods: This randomized controlled study was carried out in the Obstetrics and Gynecology. Department of C.U. Shah Medical College, Surendranagar, from 23th August 2017 to 20th August 2018. Results: Amongst the 100 participants, 50 induction is done with tab. Misoprostol and 50 induction done with EASIBC. Success rate is higher in tab. Misoprost which is 90.20% and in EASIBC is 75.51%. There were longer induction abortion interval in EASIBC: Need for curettage among Misoprostol is 5 and EASIBC is 9. Major complication like PPH occurred in two cases in induction with tab. Misoprostol, which is managed by further intervention and no death occurred. No major complication occurred in induction with EASIBC. Conclusions: Excluding the side effects and complications, which are manageable induction with tab. Misoprostol is better than EASIBC in terms of induction abortion interval, effectiveness, acceptability.